Preclinical medical students perception about their educational environment based on DREEM at a Private University, Malaysia (Bangladesh Journal of Medical Science, 2017)
Background: Educational environment is one of the important elements to students success. Student satisfaction is a significant indicator of learning quality and is related to several outcomeObjective: The cross-sectional descriptive study was done to measure the preclinical medical students perception of their educational environment at Faculty of Medicine (FOM), SEGi University.Methods: For measuring perception, the validated fifty Items English version of Dundee Ready Education Environment Measure (DREEM) questionnaire was administered among Year 1 and 2 students (N-170). Data was analyzed by SPSS software V 22. The Independent t test was used to check the significance at 95% CI.Results: The response rate of the study was good (90.6%). The mean DREEM score was 126.78/200(19.501) indicating an overall positive perception of educational environment among students. The mean scores for Year1 and 2 were 123.98/200(2.623) and128.17/200(1.952) respectively which is not statistically significant (p> 0.05). Students perceptions of educational environment in all five Domains of DREEM is positive. The year wise perception scores are not statistically significant in four Domains (p> 0.05) but the difference is significant (P 3.00 indicates strong and nine Items scored < 2.00 indicate the problem areas in the educational environment of FOM. Fourty Items scored 2-3 considered areas needed to be improved.Conclusion: Although the educational environment of FOM was found to be positive, it requires improvement as identified by the students. The faculty should address various important issues highlighted by the students to foster an excellent environment for promoting the effective learning.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.496-504